Magistratura e poder: reflexões sociológicas sobre os efeitos da judicialização no campo jurídico brasileiro - Fittipaldi, Paula Ferraço (2013)
The present research proposes to search for elements capable of making possible a new way of understanding the phenomenon of judicialization in Brazil, using the analysis of the basic concepts of Bourdieu's theory: "social field", "capital" and "habitus". Starting from the perspective of the theory proposed by Pierre Bourdieu, the judicialization, as a means of reproduction / reaffirmation of shared habitus by magistrates, can be considered as an interested act of the Judiciary in order to maintain the monopoly of jurisdiction and the consequent accumulation of power (symbolic capital) both in the internal structure of the legal field and in relation to society and the State? The choice of the dialectical method intends to make viable the analysis of the judicialization from the point of view of the Bourdieusian theory, confronting, at any moment, these two realities. In the first chapter will be built the whole theoretical contribution of work in the conceptions established by Bourdieu, based on the understanding of three indispensable concepts: social field, capital and habitus. Bourdieu presupposes the existence of social fields that interact at all times in the social structure. From this interaction there is a great dispute for the imposition of what Bourdieu called habitus, understood as the way of thinking and acting of each group. It is a true scheme of perception of reality, aimed at giving feedback and increasing the power of a given field against the social structure through the use of symbolic capital. The second chapter will analyze the process of redemocratization in Brazil and the expansion of the Law that it has provided, observing the historical characteristics present in our society. This expansion of law has led to the strengthening of the entire legal field, making it an indispensable means to achieve the materialization of constitutionally foreseen rights, outlining the phenomenon of judicialization. To understand judicialization by confronting it with the perspective of Bourdieusian theory, it is necessary to seek the vision constructed by some constitutional authors and authors of the social sciences, which will give us a notion of the theoretical inconsistencies that rest on the theme. The third and final chapter will deal with the judicialization from a perspective of the judiciary as a profession, own interests in search of valorization and power, resting in their hands the monopoly of jurisdictional provision. Finally, we will present the results obtained from interviews conducted with law professionals in search of elements that confirm the hypothesis of the present study, capable of demonstrating that the judicialization can not be seen as a centralizing action of the judiciary as a result of the inefficiency of the Executive and Legislative, but it must be seen as a an action aimed at strengthening this professional group, which is the judiciary.